FUNGSI MANAJEMEN KEPALA MADRASAH DALAM MENINGKATKAN KINERJA GURU DI MA DDI DARUN NAJAH KALOLING - FITRIYANI SAENI (UNISAN JURNAL, 2025)
The purpose of this study was to find out and describe the principal’s management function in improving teacher performance and to find out the supporting factors and inhibiting factors for teacher performance at MA Darun Najah Kaloling. This type of research is a qualitative research and is descriptive in nature, namely research that describes the management function of the Principal in improving the performance of MA Darun Najah Kaloling teachers. Data collection methods in this study are observation, interviews, and documentation. The method of data analysis is done by processing data (selecting, classifying, summarizing results, and making data reduction). Based on the results of the description that has been described, it shows that the Principal has carried out the stages of the management function well from the planning stage to the Controlling stage, but in practice sometimes there are obstacles, this is due to the lack of professional teachers, the lack of infrastructure, there are still teachers. who do not understand lesson plans and are reluctant to make lesson plans, the teacher’s lack of awareness of discipline in teaching. The teacher’s ability to evaluate learning is not yet comprehensive, some of it still leads to cognitive aspects and psychomotor aspects are not given enough attention. MA Darun Najah Kaloling includes: sincerity to work, respect for teachers and factors inhibiting teacher performance include: minimal facilities and infrastructure